Purification of a fourth glucosyltransferase from Streptococcus sobrinus. - Yamashita, Y (1989)
Recently, we found a novel primer-independent, water-soluble glucan synthase as a fourth glucosyltransferase (GTF) in a culture supernatant of strain AHT-k of Streptococcus sobrinus (Y. Yamashita, N. Hanada, and T. Takehara, Biochem. Biophys. Res. Commun. 150:687-693, 1988). In the present study, four kinds of purified GTFs, including the novel GTF, were prepared. They were composed of two primer-dependent GTFs and two primer-independent GTFs. Of the primer-dependent GTFs, one was a water-insoluble glucan synthase and the other was a water-soluble glucan synthase; both of the primer-independent GTFs were water-soluble glucan synthases (GTF-Sis). Using antisera against four purified GTFs, we concluded that the immunological properties of each were completely different from those of the others. Additionally, it was shown that the novel GTF-Si, which was previously shown to have a molecular weight of 137,000, was proteolytically degraded and could be isolated at a molecular weight of 152,000 and that Streptococcus cricetus secreted an enzyme that immunologically cross-reacted with GTF-Si. While the product of the novel GTF-Si was not an effective primer for both of the primer-dependent enzymes (water-soluble and -insoluble glucan synthases), the product of the enzyme affected the molecular size of the products of the other GTF-Sis.